Honest fitness advertisement in European badgers (Meles meles) - Allen, TM (2020)
By using European badgers (Meles meles) as a model species, my thesis examines how wild mammalian populations utilise olfactory communication via specialised glandular secretions and metabolic by-products when advertising fitness-related information to conspecifics. This research utilised bomb calorimetry to quantify energetic content within subcaudal gland secretion (a uniquely evolved scent gland), enzyme immunoassays to measure sex-steroid levels within urine, and scent-provisioning experiments which assessed behavioural responses to particular scent marks.